Dynamics of gaseous oxidized mercury at Villum Research Station during the High Arctic summer - Pernov, Jakob Boyd; Jensen, Bjarne; Massling, Andreas; Thomas, Daniel Charles; Skov, Henrik (Atmospheric chemistry and physics, 2021)
While much research has been devoted to the subject of gaseous elemental mercury (GEM) and gaseous oxidized mercury (GOM) in the Arctic spring during atmospheric mercury depletion events, few studies have examined the behavior of GOM in the High Arctic summer. GOM, once deposited and incorporated into the ecosystem, can pose a threat to human and wildlife health, though there remain large uncertainties regarding the transformation, deposition, and assimilation of mercury into the food web. Therefore, to further our understanding of the dynamics of GOM in the High Arctic during the late summer, we performed measurements of GEM and GOM, along with meteorological parameters and atmospheric constituents, and utilized modeled air mass history during two summer campaigns in 2019 and 2020 at Villum Research Station (Villum) in northeastern Greenland. Seven events of enhanced GOM concentrations were identified and investigated in greater detail. In general, the common factors associated with event periods at ground level were higher levels of radiation and lower H2O mixing ratios, accumulated precipitation, and relative humidity (RH), although none were connected with cold temperatures. Non-event periods at ground level each displayed a different pattern in one or more parameters when compared to event periods. Generally, air masses during event periods for both campaigns were colder and drier, arrived from higher altitudes, and spent more time above the mixed layer and less time in a cloud compared to non-events, although some events deviated from this general pattern. Non-event air masses displayed a different pattern in one or more parameters when compared to event periods, although they were generally warmer and wetter and arrived from lower altitudes with little radiation. Coarse-mode aerosols were hypothesized to provide the heterogenous surface for halogen propagation during some of the events, while for others the source is unknown. While these general patterns were observed for event and non-event periods, analysis of individual events showed more specific origins. Five of the seven events were associated with air masses that experienced similar conditions: transported from the cold, dry, and sunlit free troposphere. However, two events experienced contrasting conditions, with air masses being warm and wet with surface layer contact under little radiation. Two episodes of extremely high levels of NCoarse and BC, which appear to originate from flaring emissions in Russia, did not contribute to enhanced GOM levels. This work aims to provide a better understanding of the dynamics of GOM during the High Arctic summer.